Improvement of coal flotation by exposure of the froth to acoustic sound. (1st July 2021) - Ng, Chun Yong; Park, Hangil; Wang, Liguang
Highlights: Sound can improve the combustible recovery and kinetics of coal flotation. Sound can reduce reagent and air consumption without sacrificing flotation efficiency. Sound is a potential solution to the overfrothing issue in coal flotation. Abstract: Simultaneously improving coal flotation performance and the subsequent froth breakdown is challenging. The present work addresses this challenge by developing and evaluating a non-chemical approach based on the stabilization effect of acoustic sound on flotation froth. The effectiveness of this approach for improving coking coal flotation at different frother concentrations (10–25 ppm MIBC), collector dosages (0–400 g diesel/t) and aeration rates (1.2–2.2 cm/s) was demonstrated at laboratory scale and in batch mode, with a loudspeaker being placed in air above the flotation cell lip. It was found that at any operating condition tested, the use of sound could improve the flotation performance including the final combustible recovery, apparent flotation rate constant and separation efficiency rate. There was no statistically significant difference in product ash content between the flotation tests with and without applying sound, except at the highest MIBC concentration tested. The images of the product froth taken before and 5-min after being discharged from the flotation cell indicated that the froth stabilization effect induced by sound would occur only within the sound field, demonstrating the potential of the approach in mitigating the overfrothing issue without sacrificing the flotation performance. The possible mechanisms of the improvement of flotation performance with applying sound and its potential of improving coal flotation practice through reducing reagent and air consumption were discussed.